Visual analysis of research hot spots, characteristics, and dynamic evolution of international competitive basketball based on knowledge mapping - Chen, B.; Chen, W.; Chu, S.; Hu, C. (SAGE open, 2021)
A total of 1,207 papers related to competitive basketball research from 1986 to 2019 were retrieved from the Web of Science database. Taking the retrieved papers as research objects, the trend chart, keyword map, and citation map of international competitive basketball research were drawn using the visual software CiteSpaceIII, and the methods of literature review, knowledge map analysis, co-occurrence analysis, citation analysis, and word frequency analysis were used. The research status and hot spots of international competitive basketball in recent 30 years are analyzed, which clarify the research context of foreign competitive basketball, reveal the research trend of international competitive basketball, and provide theoretical reference for future competitive basketball research. The research shows that (a) competitive basketball research lacks influential scientific research institutions and leading figures, and the existing research institutions are in their own way with little cooperation. (b) The hot spots of competitive basketball research are "Competitive performance," "Gender difference," "Sports injury," and so on. Co-occurrence network structure is relatively loose and the density is not high. (c) "Sports injury" has always been the hot spot and frontier of competitive basketball research, from the early rehabilitation basic research aimed at ensuring competitive participation to the fine-grained preventive research centered on "preventing diseases," and then to the interdisciplinary comprehensive research of electronic science, neuroscience, and brain science. In this process, big data research began to emerge, reflecting the research characteristics of the era of mathematics and intelligence, and also showing the future research trend and development direction of competitive basketball.